Inhibition of insulin-like growth factor receptor: end of a targeted therapy? - Pillai, Rathi N.; Ramalingam, Suresh S. (Translational Lung Cancer Research, 2012)
The Insulin-like Growth Factor 1 (IGF-1) signaling pathway activates several downstream signals important to lung cancer development and survival. IGF-1R activation has been linked to cancer risk in epidemiological studies and tumorigenesis in preclinical models. Several inhibitors of the insulin-like growth factor 1 receptor (IGF-1R) have been tested in clinical trials. Despite promising data in early phase studies, most studies of IGF-1R antagonists in combination with chemotherapy or with epidermal growth factor receptor (EGFR) inhibitors in non-small cell lung cancer (NSCLC) yielded disappointing results. Biomarker studies of clinical trials have identified IGF-1 levels as a potential marker of sensitivity to IGF-1R inhibition. Further study will need to focus on selection of NSCLC patients most likely to benefit from the addition of IGF-1R antagonists to standard therapy and the development of rational strategies for combination therapy in NSCLC.